Programa didáctico basado en solución de problemas para mejorar el aprendizaje en el área de matemática I de los estudiantes del primer ciclo de la escuela de ingeniería civil de la Universidad César Vallejo - Toribio Aranda, Billy Santos (2017)
The present research work has the purpose of demonstrating that the Didactic Program Based on Problem Solving influences significantly in the students learning in the mathematics course of the civil engineering school of the University Cesar Vallejo (2015-2016), to in this, deductive, inductive and technical methods have been used, such as: documentary analysis, entrance and exit test. The research had an experimental group of 45 students of whom applied the Didactic Program Based on Problem Solving. It used the pre experimental methodological design. It was demonstrated with the results obtained that the Didactic Program Based on Solution of Problems influences significantly in the learning of the subject of mathematics. Finally, it is concluded that quantitatively the application of the Didactic Program allowed to improve the qualifications of the students in comparison with the traditional method.